2014
DOI: 10.1152/ajpregu.00525.2013
|View full text |Cite
|
Sign up to set email alerts
|

Postexercise whole body heat stress additively enhances endurance training-induced mitochondrial adaptations in mouse skeletal muscle

Abstract: A recent study demonstrated that heat stress induces mitochondrial biogenesis in C2C12 myotubes, thereby implying that heat stress may be an effective treatment to enhance endurance training-induced mitochondrial adaptations in skeletal muscle. However, whether heat stress actually induces mitochondrial adaptations in skeletal muscle in vivo is unclear. In the present study, we report the novel findings that 1) whole body heat stress produced by exposure of ICR mice to a hot environment (40°C, 30 min/day, 5 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
66
3
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 51 publications
7
66
3
2
Order By: Relevance
“…However, a recent study reported decreased AMPK signalling in plantaris and soleus muscles of mice subjected to acute heat exposure (Tamura et al, 2014). Chronic exposure (5 weeks) resulted in increased CS and β-HAD activities as well as protein content of respiratory complexes I-V, however AMPK signalling was not investigated following chronic exposure in this study (Tamura et al, 2014). This disparity in results could be a function of the experimental models used (i.e.…”
Section: Role Of Temperature In Pgc-1α Mediated Adaptations Passive Hmentioning
confidence: 62%
See 4 more Smart Citations
“…However, a recent study reported decreased AMPK signalling in plantaris and soleus muscles of mice subjected to acute heat exposure (Tamura et al, 2014). Chronic exposure (5 weeks) resulted in increased CS and β-HAD activities as well as protein content of respiratory complexes I-V, however AMPK signalling was not investigated following chronic exposure in this study (Tamura et al, 2014). This disparity in results could be a function of the experimental models used (i.e.…”
Section: Role Of Temperature In Pgc-1α Mediated Adaptations Passive Hmentioning
confidence: 62%
“…For instance, in studies using cell culture and animal models, mitochondrial biogenesis has shown to be up-regulated following both heat and cold exposures through PGC-1α dependant mechanisms similar to that observed following exercise (Bruton et al, 2010;Liu & Brooks, 2012;Puigserver et al, 1998;Tamura et al, 2014;Wu et al, 1999). However, when administered following exercise, both heat and cold interventions have demonstrated contradictory results, with some studies showing beneficial, while others detrimental effects on PGC-1α and/or muscle aerobic performance (Ihsan et al, 2014;Slivka et al, 2013;Slivka et al, 2012;Tamura et al, 2014;Yamane et al, 2006). Taken together, these studies highlight the potential of these modalities to both enhance and diminish mitochondrial adaptations to training, as well implicating PGC-1α as a key target in these mechanisms.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations